1997
DOI: 10.1071/wr96021
|View full text |Cite
|
Sign up to set email alerts
|

Social Organisation and Warren Use of the Burrowing Bettong, Bettongia lesueur (Macropodoidea : Potoroidae)

Abstract: This study describes the use of warrens and aspects of the social organisation of a population of the burrowing bettong, an endangered potoroid. Observations were made on 14 animals, maintained in a 4-ha enclosure of natural vegetation at Shark Bay, Western Australia. The population divided into three social groups, each of one male and one to many females. Individual bettongs used 1–10 warrens over a period of five months. Males changed warrens more often than females. Some females regularly shared warrens wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…Burrowing bettongs are social animals that live in family groups and spend the daylight hours underground in multi-entranced warren systems [40]. They exhibit high burrow fidelity and at Arid Recovery they move on average 320 m from their burrows to their centres of activity [41].…”
Section: Methodsmentioning
confidence: 99%
“…Burrowing bettongs are social animals that live in family groups and spend the daylight hours underground in multi-entranced warren systems [40]. They exhibit high burrow fidelity and at Arid Recovery they move on average 320 m from their burrows to their centres of activity [41].…”
Section: Methodsmentioning
confidence: 99%
“…Social organisation and warren use of a semi-captive population at Shark Bay have been described by Sander et al (1997) and warren use and home range have been described for Barrow Island by Short and Turner (1990), at Heirisson Prong by Robley (2000) and within enclosures at the Arid Recovery site in South Australia by Finlayson and Moseby (2004). The latter populations were sourced from islands in Shark Bay.…”
Section: Discussionmentioning
confidence: 99%
“…This extensive loss of fur made them susceptible to exposure in cold weather. In contrast, Sander et al (1997) found what appeared to be extended associations between mothers and daughters in B. lesueur. This included warren sharing and close association when feeding.…”
Section: Recruitmentmentioning
confidence: 65%
“…In this way the victim is worn out; and, plucked of its fur, and scored by deep furrows produced by its rivals strong claws, it dies of exhaustion (Jones 1924). Males of B. lesueur in captivity are known to establish dayranges exclusive of other males that encompass a cluster of warrens occupied by up to six females (Sander et al 1997).…”
Section: Sex Ratiomentioning
confidence: 99%
See 1 more Smart Citation